Penggunaan Media Labirin Untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas II Di Sd Al-Baitul Amien 02 Jember - Izza Afkarina; Soesy Sri Wulandari; Much Arsyad Fardani (Jurnal Prasasti Ilmu, 2025)
This study aims to describe the improvement of student learning outcomes by applying labyrinth media to mathematics learning in class II of SD Al-Baitul Amien 02 Jember. The research method uses Classroom Action Research (CAR). Each cycle consists of two meetings including planning, implementation, observation, and reflection. The test results in the pre-cycle learning outcome study showed that the percentage of students who completed was 32.32%, the percentage of incomplete was 67.67%, so that the pre-cycle score was 59.10 with the category of needing guidance. learning outcomes in cycle I, the percentage of complete was 65.05%, the percentage of incomplete was 34.94% with the category of needing guidance. It can be concluded that learning by applying labyrinth media to addition and subtraction materials can improve student learning outcomes.